2017
DOI: 10.1038/srep39822
|View full text |Cite
|
Sign up to set email alerts
|

Atypical developmental trajectory of local spontaneous brain activity in autism spectrum disorder

Abstract: Autism spectrum disorder (ASD) is marked by atypical trajectory of brain maturation, yet the developmental abnormalities in brain function remain unclear. The current study examined the effect of age on amplitude of low-frequency fluctuations (ALFF) in ASD and typical controls (TC) using a cross-sectional design. We classified all the participants into three age cohorts: child (<11 years, 18ASD/20TC), adolescent (11–18 years, 28ASD/26TC) and adult (≥18 years, 18ASD/18TC). Two-way analysis of variance (ANOVA) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 76 publications
(103 reference statements)
7
54
1
2
Order By: Relevance
“…As we expected, the cerebellum spontaneous activity was associated with clinical severity and functional de cits, which is in good agreement with earlier ALFF analysis (Guo, et al, 2017) and task-dependent fMRI study (Murphy, et al, 2017). Speci cally, we found that SRS cognition score T was only positively related to cerebellum vermis 4 5, which were not obtained in NCs.…”
Section: Discussionsupporting
confidence: 92%
“…As we expected, the cerebellum spontaneous activity was associated with clinical severity and functional de cits, which is in good agreement with earlier ALFF analysis (Guo, et al, 2017) and task-dependent fMRI study (Murphy, et al, 2017). Speci cally, we found that SRS cognition score T was only positively related to cerebellum vermis 4 5, which were not obtained in NCs.…”
Section: Discussionsupporting
confidence: 92%
“…Significant reductions in GABA expression have been found using MR spectroscopy (117) as well as in postmortem brain tissue of individuals with ASD (118) (Figure 5F). The co-localized pattern of deficits in cell-migration and GABA signaling in the cortex of individuals with ASD suggests that these deficits occur early in cortical development, potentially leading to persistent E/I imbalances throughout development (119121) and altered brain connectivity in ASD (9, 122, 123). Crucially, these types of developmental aberrancies in local brain circuits are likely to influence global circuit function especially if they occur in widely connected hubs such as the PCC (64, 108, 110).…”
Section: Neurophysiological Basis Of Dmn Dysfunction In Asdmentioning
confidence: 99%
“…As a result of different maturation rates, the pattern of gray‐matter group differences is expected to change as a function of the age. As a final example, in an fMRI study examining RS activity in controls and individuals with ASD, Guo et al . showed that the pattern of group differences changed as a function of age in some but not all brain regions.…”
Section: Beyond Electrophysiologymentioning
confidence: 99%